Optimising the use of note-taking as an external cognitive aid for increasing learning - MAKANY, Tamas (Institutional Knowledge at Singapore Management University, 2009)
Taking notes is of uttermost importance in academic and commercial use and success. Different techniques for note-taking utilise different cognitive processes and strategies. This experimental study examined ways to enhance cognitive performance via different note-taking techniques. By comparing performances of traditional, linear style note-taking with alternative non-linear technique, we aimed to examine the efficiency and importance of different ways of taking notes. Twenty-six volunteer adult learners from an information management course participated in this study. Cognitive performance scores from a traditional linear note-taking group were compared with another group by using a commercially available non-linear note-taking technique. Both groups were tested in two settings: after a classroom lecture and a panel forum discussion. Tasks included measures on story comprehension, memory, complexity of mental representations and metacognitive skills. Data analysis revealed that the non-linear note-takers were significantly better than the linear group both in terms of the quantity and the quality of the learned material. This study demonstrates the importance of using cognitively compatible note-taking techniques. It identifies the cognitive mechanisms behind effective note-taking and knowledge representation. Using such techniques enables deeper understanding and more integrated knowledge management.